Spiritualiteit – ’n perspektief uit die Oude Testament - Snyman, S. D. (In die Skriflig, 1997)
Spirituality is defined as coram Deo, that is, living in the presence of God. In this article it is argued that within the South African context, the Old Testament is not given due regard in the scholarly debate on spirituality. The foundation of an Old Testament spirituality is God revealing his name in Exodus 3:14-15 as the ever-present God. Following the tripartite division of the Old Testament it is argued that the Torah can be seen as a call to obedience within covenantal structures. The prophets can be seen as proclaimers of God's Word. Jeremiah and Habakuk are examples of prophets who were not at ease with God and his actions. The doxologies found in prophetic literature are also important aspects of an Old Testament spirituality. The contribution of the Ketubim to the theme of spirituality can be summarised by the concepts of prayer and life. This preliminary investigation into the contribution the Old Testament can make on the issue of spirituality shows that much can be gained by taking the Old Testament into full account when reflecting on spirituality.
free